Electricity system and emission impact of direct and indirect electrification of heavy-duty transportation. (1st April 2019) - Keller, Victor; Lyseng, Benjamin; Wade, Cameron; Scholtysik, Sven; Fowler, McKenzie; Donald, James; Palmer-Wilson, Kevin; Robertson, Bryson; Wild, Peter; Rowe, Andrew
Abstract: Widespread adoption of alternative fuel vehicles in the heavy-duty transportation sector could significantly mitigate carbon emissions of this important sector. However, the extent of emission reductions and their feasibility will depend on the carbon intensity of the electricity system, alternative fuel vehicle technologies and vehicle charging profiles. Utilizing a capacity expansion and dispatch model, this study compares alternative pathways for decarbonizing the electricity and heavy duty transportation sector to 2060. Scenarios with battery electric vehicles, with three alternative charging profiles, and fuel cell vehicles are compared with 0 and 150 /tCO2 carbon taxes. Results show that adoption of alternative fuel vehicles in the absence of carbon taxes leads to, in the best case, cumulative emission reductions of 3% relative to a reference scenario due to the reliance on natural gas generation. In scenarios with a tax of 150/tCO2e, results show that adoption of fuel cell vehicles achieves the highest emission reduction of all studied scenarios with cumulative reductions of 43% from the reference scenario and the lowest carbon abatement cost, at 15.2 /tCO2e . The flexibility of electrolysers allows low cost renewable energy to be stored as hydrogen thereby avoiding investment in higher cost and higher emitting technologies. Highlights: Use of fuel cell vehicles leads to lower system carbon abatement cost than battery electric vehicles. Electrolysers lead to higher penetration of renewable energy in electricity system. Hydrogen storage used for seasonal storage of solar energy. Electrification of heavy duty vehicles leads to little benefits without additional policy.